2018
DOI: 10.4103/jmu.jmu_16_17
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic findings of malignant appendix tumors in seven cases

Abstract: We report the sonographic features of confirmed malignant appendiceal tumors in seven cases. The histologic diagnoses of these tumors were mucinous cystadenocarcinoma (n = 2), colonic type adenocarcinoma (n = 4), and signet-ring cell carcinoma (n = 1). The 2 mucinous cystadenocarcinomas showed mucocele type, which had markedly enlarged inner luminal diameters (mean, 23 mm; range, 15–31 mm) and thick, irregular walls (mean wall thickness, 5.5 mm; range, 5–6 mm). In contrast, the 5 nonmucinous carcinomas (4 aden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…[21] A previous research confirmed that colon cancer presents the following features in high-resolution ultrasound: heterogeneous hypoechoic masses, irregular wall thickening, and absence of lamellar walls. [21] Cho et al described the distinction between neoplastic and non-neoplastic inflammatory responses of the appendix. Firstly, the true lumen diameter of neoplastic inflammation of the appendix is typically smaller than that of acute appendicitis.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…[21] A previous research confirmed that colon cancer presents the following features in high-resolution ultrasound: heterogeneous hypoechoic masses, irregular wall thickening, and absence of lamellar walls. [21] Cho et al described the distinction between neoplastic and non-neoplastic inflammatory responses of the appendix. Firstly, the true lumen diameter of neoplastic inflammation of the appendix is typically smaller than that of acute appendicitis.…”
Section: Discussionmentioning
confidence: 97%
“…The ultrasonographic manifestations of non-mucinous carcinoma of the appendix (including adenocarcinoma and SRCC) are relatively small intestinal lumen diameter, appendix wall thickening or submucosal hypoecho. [21] A previous research confirmed that colon cancer presents the following features in high-resolution ultrasound: heterogeneous hypoechoic masses, irregular wall thickening, and absence of lamellar walls. [21] Cho et al described the distinction between neoplastic and non-neoplastic inflammatory responses of the appendix.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiological features for appendiceal tumours in ultrasound and computed tomography (CT) are nonspecific and occult [ 26 , 27 ]. But depending on the entity of appendiceal malignancies some sonographic features such as enlarged or small inner luminal diameter, thick and irregular appendix wall, loss of layer pattern of the appendix wall, and even hypoechogenicity are described [ 26 ]. In addition, infiltration of the periappendiceal fat or even abscess formation with suspicion of appendix perforation may be seen in cases of appendiceal malignancies [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…But depending on the entity of appendiceal malignancies some sonographic features such as enlarged or small inner luminal diameter, thick and irregular appendix wall, loss of layer pattern of the appendix wall, and even hypoechogenicity are described [ 26 ]. In addition, infiltration of the periappendiceal fat or even abscess formation with suspicion of appendix perforation may be seen in cases of appendiceal malignancies [ 26 ]. Findings in abdominal CT scans are again depending on the underlying type of malignancy and reach from hyperenhancement, nodular wall thickening, calcification, mucocele, lymphadenopathy, periappendiceal fat infiltration, or tumour mass [ 27 ].…”
Section: Introductionmentioning
confidence: 99%